ANALISIS PENERAPAAN MODEL PEMBELAJARAN BERBASIS MASALAH DALAM MENGEMBANGKAN KETERAMPILAN BERPIKIR KRITIS PADA PEMBELAJARAN PPKN - Lisarti, Lisarti; Sulistyarini, Sulistyarini; Rosyid, Rum (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis thesis is entitled "Applying Problem Based Learning Model Critical Thinking Skills to Learning PPKn in Class X Pontianak 9 High School". The method used in this study is descriptive research method with the form of research used in survey research. The subjects of this study were class X students of SMA Negeri 9 Pontianak. Data collection techniques used in this study are direct communication techniques, observation, and tests. The results of the study can be concluded that the application of a problem-based model of critical thinking skills can improve learning outcomes in learning class X PPKn Pontianak 9 SMA. Planning for the implementation of a problem-based learning model in developing critical thinking skills in PPKN learning in class X Pontianak 9 Public High School. It has been in accordance with 2013 Curriculum, which refers to more creative learning goals and many variations.Â Keyword :Problem Based Learning Model, Critical Thinking, Civics Learning